Peningkatan Kesehatan Gigi dan Mulut Melalui Revitalisasi Usaha Kesehatan Gigi Sekolah di SDN Pasar Kamis 2 Kabupaten Banjar - Isnur Hatta; Riky Riky; Aulia Azizah; Nida Amalia (Universitas Lambung Mangkurat, 2023)
Pasar Kamis 2 elementary school is one of the elementary schools in Kertak Hanyar District that has not implemented a phase III school dental health program, so it is necessary to revitalize the school dental health program. The revitalization of school dental health programs aims to revive promotional programs for dental and oral health in elementary schools. The method applied for this community service activity is by carrying out promotional activities in the form of teacher training for school dental health businesses, training for little doctors, health promotion through the media snakes and ladders and the song SIGIBER, as well as joint toothbrushing activities. Preventive activities carried out include carrying out dental and oral health screening and carrying out fissure sealant treatment and atraumatic restorative treatment based on the results of the screening. Evaluation of community service activities is carried out by measuring the results of pretest and posttest students' knowledge and analyzing the provision of preventive measures to students. The results of this service show that there is a difference in knowledge before and after being given health promotion interventions, as well as an improvement in students' dental and oral health after preventive measures are given in the form of pit and fissure sealants and atraumatic restorative treatment. Revitalization of school dental health businesses is important so that promotional activities for dental and oral health in the school environment are not neglected so that they can improve dental and oral health and school children's achievement in learning.